anonymous
  • anonymous
How do i solve this equation and check for extraneous solutions?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
4x+3=9+2x. -3 from both sides
anonymous
  • anonymous
\[\sqrt[3]{4x-2}=2\sqrt[3]{x+6}\]
anonymous
  • anonymous
i'm sorry. this was the kind of problem I was working on.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
x=3 and x=-2
anonymous
  • anonymous
Can you explain to me how you did that? @kathy0514
anonymous
  • anonymous
separate it into 2 equations when there is an absolute value 4x+3=±(9+2x) solve 4x+3 = 9+2x and 4x+3 = -(9+2x)
anonymous
  • anonymous
x=4 does not work
anonymous
  • anonymous
ust get x by itself by combining like terms example: 3x-1 = 5 add 1 to both sides to move 1 to right side divide by 3 to both sides to move 3 to right side
anonymous
  • anonymous
combine the "x" terms
anonymous
  • anonymous
move 2x to left side
anonymous
  • anonymous
you added , always do the inverse(opposite) operation
anonymous
  • anonymous
4x = 6 +2x --> subtract 2x 4x = 6-2x --> add 2x
anonymous
  • anonymous
same reason you took -3 from both sides earlier ....to cancel the 3 on right side now take "-2x" to cancel the 2x on right side
anonymous
  • anonymous
4x+3 = -(9+2x) distribute 4x+3 = -9 -2x -3 to both sides 4x = -12 -2x 2x to both sides 6x = -12 divide x = -2
anonymous
  • anonymous
don't forget to distribute the negative
anonymous
  • anonymous
understood?
anonymous
  • anonymous
one question that i have is how did you get 4x+3=9+2x
anonymous
  • anonymous
but yes and Thankyou
anonymous
  • anonymous
@kathy0514
anonymous
  • anonymous
x=2 -4x+3=2x-9 -2x -2x -6x+3=-9 -3 -3 -6x=-12 / -6 = 2 x=2
anonymous
  • anonymous
ok good. have a great day
anonymous
  • anonymous
Tanks you too
anonymous
  • anonymous
thanks
anonymous
  • anonymous
I'm sorry but while I was reviewing the question again. I can't find out how you got 4x+3 insted of 4x-2
anonymous
  • anonymous
@kathy0514
anonymous
  • anonymous
x=2 -4x+3=2x-9 -2x -2x -6x+3=-9 -3 -3 -6x=-12 / -6 = 2 x=2
anonymous
  • anonymous
Okay, thanks

Looking for something else?

Not the answer you are looking for? Search for more explanations.